Visual Attention Cut Points for Driver Fitness in Parkinson's Disease. (October 2019) - Classen, Sherrilene; Brumback, Babette; Crawford, Karla; Jenniex, Sara
This study determined whether the Useful Field of View™ Risk Index (UFOV RI) adds value as a predictor of on-road outcomes in drivers with Parkinson's disease (PD) when considered with age, gender, and disease severity and compared with community-dwelling older drivers (Controls). A total of 101 PD drivers and 138 Controls underwent a comprehensive driving evaluation, including an on-road assessment. Logistic regression analyses determined the associations of age, gender, visual attention, and disease severity to on-road outcomes. Receiver operating characteristic curve analyses determined the optimal UFOV RI cut points to predict on-road outcomes. Above adding age and gender, the UFOV RI alone predicted on-road outcomes in PD, while the UFOV RI and age predicted on-road outcomes in Controls. Regardless of disease severity, visual attention was more impaired in PD than in Controls. The UFOV RI cut point of 3 provided the fewest misclassifications ( n = 25) in PD. The UFOV RI is a valid screening predictor of on-road outcomes across PD drivers of different disease severity, but has moderate sensitivity and specificity.